From Protest to Occupation: Analyzing the Social and Political Implications of the Capitol Hill Autonomous Zone - Firsty Chintya Laksmi Perbawani; Ofel Abiwada Abimanyu; Angelina Febriola Putri (Nusantara Science and Technology Proceedings, 2022)
Capitol Hill Autonomous Zone (CHAZ) or Capitol Hill Occupied Protest (CHOP) was a self-proclaimed autonomous zone established in June 2020 in Seattle, Washington. After a week of fraught interactions between demonstrators and police in riot gear, protesters established the area after the Seattle Police Department abandoned the East Precinct. The area, which encompassed two intersections at the extremities of Cal Anderson Park and the roadways leading to them, was self-organized and lacked formal leadership. This research paper examines the formation of CHAZ, its processes, and its effects on Seattle's later growth. This research paper contends, utilizing Mancur Olson's Collective Action Theory and a qualitative approach, that CHAZ was established as a result of the local government's minimal effort to engage with the local community. Furthermore, Michael Lipsky's conception of protest as a political resource bolsters CHAZ's demonstration of how protest can influence decision-makers through indirect channels, such as occupation. CHAZ ultimately succeeded in persuading the public and influencing municipal policies to be more equitable.